Male lion on a kopje in Serengeti National Park - Kerr, Jeremy (Université d'Ottawa | University of Ottawa, 2019)
A lion at sunset, relaxing on a kopje in Serengeti National Park. Female lion is just at the bottom left edge of the photo. Taken August 28, 2019. A pair of lions were mating by this kopje in Serengeti National Park near the end of the day. Lion mating involves repeated copulation over the course of several hours. The lioness is nearby, lying also on the kopje.
Keywords: Field course; Africa; African Ecology; Tanzania; Lion; Serengeti; kopje; Panthera leo; national park; OUPFB; Ontario Universities Program in Field Biology